Intersex Initiative: From "Intersex" to "DSD" - Koyama, Emi (2006)
keynote speech presented at Translating Identity conference held at University of Vermont in February 2006.
Keywords: EDI; LGBTQIA2+; approches et analyses; capacitisme; cours; discipline; intersexuation; patriarcat; premier cycle; queer; sciences humaines; soc2014; systèmes d'oppressions; thématiques; violences; violences médicales; études critiques du handicap

Crip theory: cultural signs of queerness and disability - MacRuer, Robert (Cultural front, 2006)
A bold and contemporary discourse of the intersection of disability studies and queer studies Crip Theory attends to the contemporary cultures of disability and queerness that are coming out all over. Both disability studies and queer theory are centrally concerned with how bodies, pleasures, and identities are represented as “normal” or as abject, but Crip Theory is the first book to analyze thoroughly the ways in which these interdisciplinary fields inform each other. Drawing on feminist theory, African American and Latino/a cultural theories, composition studies, film and television studies, and theories of globalization and counter-globalization, Robert McRuer articulates the central concerns of crip theory and considers how such a critical perspective might impact cultural and historical inquiry in the humanities. Crip Theory puts forward readings of the Sharon Kowalski story, the performance art of Bob Flanagan, and the journals of Gary Fisher, as well as critiques of the domesticated queerness and disability marketed by the Millennium March, or Bravo TV’s Queer Eye for the Straight Guy. McRuer examines how dominant and marginal bodily and sexual identities are composed, and considers the vibrant ways that disability and queerness unsettle and re-write those identities in order to insist that another world is possible.
Keywords: EDI; LGBTQIA2+; approches et analyses; art; cours; crip; discipline; militance; premier cycle; queer; santé; soc2014; thématiques; études critique du handicap; études littéraires

Queering the Crip or Cripping the Queer?: Intersections of Queer and Crip Identities in Solo Autobiographical Performance - Sandahl, Carrie (GLQ: A Journal of Lesbian and Gay Studies, 2003)
As the interdisciplinary field of disability studies develops its own theoretical paradigms, it necessarily borrows from various sources. Such borrowing means that disability scholars have not had to reinvent the wheel but have been able to build on the conceptual foundations of identity-based theories that have grown out of other interdisciplinary fields, such as gender studies and critical race studies. But disability studies offers as much to its predecessors as it borrows from them. This essay explores the productive reciprocity between queer theory and disability studies, queer identity and crip identity, queer activism and crip activism.
Keywords: EDI; LGBTQIA2+; approches et analyses; arts; capacitisme; care; corps; cours; crip; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit4700; militance; premier cycle; queer; ressource en ligne; santé; systèmes d'oppressions; thématiques; théâtre; études littéraires

Integrating Disability, Transforming Feminist Theory - Garland-Thomson, Rosemarie (NWSA Journal, 2002)
This essay aims to amplify feminist theory by articulating and fostering feminist disability theory. It names feminist disability studies as an academic field of inquiry, describes work that is already underway, calls for needed study and sets an agenda for future work in feminist disability studies. Feminist disability theory augments the terms and confronts the limits of the ways we understand human diversity, the materiality of the body, multiculturalism, and the social formations that interpret bodily differences. The essay asserts that integrating disability as a category of analysis and a system of representation deepens, expands, and challenges feminist theory. To elaborate on these premises, the essay discusses four fundamental and interpenetrating domains of feminist theory: representation, the body, identity, and activism, suggesting some critical inquiries that considering disability can generate within these theoretical arenas.
Keywords: EDI; activisme; approches et analyses; corps; cours; discipline; militance; premier cycle; queer; ressource en ligne; santé; sciences humaines; sciences sociales; sex1920; thématiques; études critiques du handicap; études féministes